Photographic Eyewitness Identification and the Presumption of Innocence - Janaina Matida; William Weber Cecconello (Revista Brasileira de Direito Processual Penal, 2021)
Eyewitness identification is an important criminal evidence for the justice system, however, innocent people can be identified for crimes that they did not commit. Procedures adopted for recognition may increase the likelihood of false identification, such as the presentation of a single suspect (show-up), or multiple suspects at the same time (suspects album). In a context of patent irregularities, eyewitness identification through photographs are believed to be less reliable in Brazil, where the live identification is preferred. In this paper, from legal epistemology and psychology of testimony, we approach the advantages and possibilities of photo eyewitness identification as a method to enable a fair lineup procedure. Empirical data from experimental and cognitive psychology are presented that confirm the results of photographic method for eyewitness identification and, in the end, arguments are presented for the adoption towards the construction of a Brazilian democratic criminal code, which ensures effective reach to the presumption of innocence.